The Implementation of Small-Side Games Practise Model on Improving Students Intrinsic Motivation and Social Behavior - Lugaya, Yuga Rahmatullah; ., Komarudin; Fitri, Mustika (Universitas Pendidikan Indonesia, 2019)
The aim of this study was to determine the effect of small-side games on intrinsic motivation and social behavior in physical education learning. In education, especially in Indonesia, the use of quasi experiment is highly recommended since the condition of the object of the research that often does not allow random assignments. The population of the study were students of Subang 1 Public High School who participated in the Bolabasket Extracurricular. The samples of the study were 48 students chosen by using the Random Cluster Sample technique and devided into control group and experimental group. The instruments used were IMI (Intrinsic Motivation Inventory) and SSBS (School Social Behavior Scale). The results showed that the development of the Intrinsic Motivation on experimental group is higher than the control group. The experimental group was also higher in social behaviour than the control group. The conclusion is that this study reveals the importance of interesting learning process. An interesting learning process with more values in every activity has a positive impact on the students intrinsic motivation and social behavior.